2017
DOI: 10.1007/s10509-017-3066-3
|View full text |Cite
|
Sign up to set email alerts
|

On the interplay between cosmological shock waves and their environment

Abstract: Cosmological shock waves are tracers of the thermal history of the structures in the Universe. They play a crucial role in redistributing the energy within the cosmic structures and are also amongst the main ingredients of galaxy and galaxy cluster formation. Understanding this important function requires a proper description of the interplay between shocks and the different environments where they can be found. In this paper, an Adaptive Mesh Refinement (AMR) Eulerian cosmological simulation is analysed by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Both quantities are theoretically connected with radio signals, such as the synchrotron or the H I 21-cm line emission, which raise new possibilities for detecting gas filaments. Interestingly, using a shock-finding algorithm (Planelles & Quilis 2013), Martin-Alvarez et al (2017) studied shocks in different environments and found that shocks in filaments display a spectral slope coincident with the gas matter power spectrum. That implies a consistency distribution of gas in both real and phase spaces.…”
Section: Ratio -Pwebmentioning
confidence: 99%
“…Both quantities are theoretically connected with radio signals, such as the synchrotron or the H I 21-cm line emission, which raise new possibilities for detecting gas filaments. Interestingly, using a shock-finding algorithm (Planelles & Quilis 2013), Martin-Alvarez et al (2017) studied shocks in different environments and found that shocks in filaments display a spectral slope coincident with the gas matter power spectrum. That implies a consistency distribution of gas in both real and phase spaces.…”
Section: Ratio -Pwebmentioning
confidence: 99%
“…Alternatively, galactic magnetic fields might have evolved through in-situ large amplification of weak primordial seeds (Pakmor et al 2014;Vazza et al 2014;Martin-Alvarez et al 2018); or been seeded through processes such as stellar winds, supernovae (SNe), or AGN (Beck et al 2013;Butsky et al 2017;Vazza et al 2017;Katz et al 2019) acting as small-scale batteries. Other possibilities are their generation during reionization (Durrive et al 2017), or their amplification prior to accretion onto galaxies or galaxy clusters by shock-induced turbulence (Kulsrud et al 1997;Ji et al 2016), potentially tracing the spectrum of cosmic shock waves (Martin-Alvarez et al 2017). Amongst these diverse scenarios, the main advantage provided by a primordial origin is a simultaneous explanation of the existence of cosmic, cluster, and galactic magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Sunyaev and Zeldovich, 1972;Markevitch and Vikhlinin, 2007;Bykov et al, 2008a;Kushnir and Waxman, 2009;Brüggen et al, 2012;Cavaliere and Lapi, 2013). Around galaxy clusters, strong M ≥ 10−10 2 accretion shocks should exist in a quasi-stationary way and mark the transition from smooth infalling matter to halos undergoing their virialisation process, as illustrated in the top panels of Fig.1 (Miniati et al, 2000;Ryu et al, 2003b;Pfrommer et al, 2006;Vazza et al, 2009;Planelles and Quilis, 2013;Schaal et al, 2016;Martin-Alvarez et al, 2017). The statistics of shocks in the Universe is predicted to be dominated by structure formation shocks, with only a minor contribution from non-gravitational processes, as shown in the bottom left panel of Fig.1 (e.g.…”
mentioning
confidence: 97%